ECONOMIC RELATIONS OF THE SAFAVID STATE WITH VENICE AND PORTUGAL IN THE 16TH CENTURY - OSMANOVA NUBAR ILGAR (Foundations and Trends in Modern Learning, 2025)
In the 16th century, Azerbaijan, thanks to its location on important trade routes and rich natural resources, established economic relations with European states, especially Venice and Portugal. Venetian merchants traveled to Azerbaijan via the Silk Road, transporting silk, carpets and other valuable products to European markets. These trade relations contributed to the cultural and economic integration of Azerbaijan with Western Europe. Portugal, on the other hand, had a strong position in the Indian Ocean trade and tried to establish maritime trade relations with the Safavid state. Portuguese merchants were interested in Azerbaijani products, especially through the ports of the Persian Gulf. These relations influenced the economic development of the region and increased the strategic importance of Azerbaijan. During this period, economic relations were not limited only to trade exchanges, but were also accompanied by diplomatic contacts, which indicates that Azerbaijan occupied an important place in the international trade system